System sprawozdawczości jednostki budżetowej jako źródło informacji decyzyjnej - Jurga, Agnieszka (The System of Reporting of a Budgetary Unit as a Source Of Information in a Decision-Making Process, 2006)
All budgetary units are obliged to prepare periodic budget reports which are the basic source of information on the budget execution. The reports present the course and effects of performing financial plans. Thus, they provide information which is necessary in a decision-making process, they help to control the enforcement of the decisions as well as to evaluate the justification of using the budget resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 144-149